Human coronary inflammation by computed tomography: Relationship with coronary microvascular dysfunction. (1st August 2021) - Pasqualetto, Maria Cristina; Tuttolomondo, Domenico; Cutruzzolà, Antonio; Niccoli, Giampaolo; Dey, Damini; Greco, Alessandro; Martini, Chiara; Irace, Concetta; Rigo, Fausto; Gaibazzi, Nicola
Abstract: Background A new imaging metric using coronary computed tomography angiography (CCTA), addressing the peri-coronary adipose tissue (PCAT) computed tomography (CT) attenuation, has been clinically validated. This method provides information regarding coronary inflammation. It is unclear how coronary inflammation affects microvascular function. The non-invasive evaluation of coronary flow velocity reserve is widely used in clinical practice using Doppler measurement on the left anterior descending coronary artery (CFVR-lad) during stress-echocardiography (SE). We hypothesize that coronary inflammation affects CFVR-lad and, in the absence of overt CAD, they are significantly correlated. Methods We evaluated the relationship between coronary inflammation (by PCAT CT attenuation) and coronary microvascular function (by CFVR-lad) in subjects with no or non-obstructive (diameter stenosis <70%) coronary artery disease (CAD). Results Two-hundred and two subjects were enrolled in the study. The relationship between PCAT CT attenuation and CFVR-lad show a significant inverse relationship in the entire group of subjects enrolled in the study ( r = −0.32, p < 0.001). Correlation between PCAT CT attenuation and CFVR-lad was significant in subjects with no or mild CAD-lad, while this was not the case in subjects with intermediate CAD-lad. The R and R 2 were respectively −0.40, −0.16 in subjects without CAD ( p < 0.001) and − 0.35 and − 0.12 in subjects with mild CAD-lad ( p = 0.001). Conclusions The main finding of the current study is the independent relationship between coronary microvascular function, by Doppler CFVR-lad during SE, in subjects without severely obstructive CAD in the left anterior descending coronary artery, and the level of local coronary inflammation, by PCAT attenuation measurement on CCTA. Highlights: Doppler coronary flow velocity reserve represents microcirculatory function in subjects without obstructive coronary artery disease. Peri-coronary adipose tissue attenuation on computed tomography represents coronary inflammation. These two markers did significantly correlate in subjects with no or non-obstructive coronary artery disease.